Fractionation of Hen Egg and Oat Lipids with supercritical Fluids Chemical and functional Properties of Fractions - Aro, Heikki (fi=Turun yliopisto|en=University of Turku|, 2012)
Hen eggs and oats (Avena Sativa) are important materials for the food industry. Today, instead of merely satisfying the feeling of hunger, consumers are asking for healthier, biologically active and environmentally friendly products. The growing awareness of consumers’ increasing demands presents a great challenge to the food industry to develop more sustainable products and utilise modern and effective techniques. The modification of yolk fatty acid composition by means of feed supplements is well understood. Egg yolk phospholipids are polar lipids and are used in several applications including food, cosmetics, pharmaceuticals, and special nutrients. Egg yolk phospholipids are excellent emulsifiers, typically sold as mixtures of phospholipids, triacylglycerols, and cholesterol. However, highly purified and characterised phospholipids are needed in several sophisticated applications. Industrial fractionation of phospholipids is usually based on organic solvents. With these fractionation techniques, some harmful residues of organic solvents may cause problems in further processing. The objective of the present study was to investigate the methods to improve the functional properties of eggs, to develop techniques to isolate the fractions responsible for the specific functional properties of egg yolk lipids, and to apply the developed techniques to plant-based materials, too. Fractionation techniques based on supercritical fluids were utilised for the separation of the lipid fractions of eggs and oats. The chemical and functional characterisation of the fractions were performed, and the produced oat polar lipid fractions were tested as protective barrier in encapsulation processes. Modifying the fatty acid compositions of egg yolks with different types of oil supplements in feed had no affect on their functional or sensory properties. Based on the results of functional and sensory analysis, it is evident that eggs with modified fatty acid compositions are usable in several industrial applications. These applications include liquid egg yolk products used in mayonnaise and salad dressings. Egg yolk powders were utilised in different kinds of fractionation processes. The precipitation method developed in this study resembles the supercritical anti-solvent method, which is typically used in the pharmaceutical industry. With pilot scale supercritical fluid processes, non-polar lipids and polar lipids were successfully separated from commercially produced egg yolk powder and oat flakes. The egg and oat-based polar lipid fractions showed high purities, and the corresponding delipidated fractions produced using supercritical techniques offer interesting starting materials for the further production of bioactive compounds. The oat polar lipid fraction contained especially digalactosyadiacylglycerol, which was shown to have valuable functional properties in the encapsulation of probiotics.